The research focus and frontiers in surgical treatment of essential tremor - Zhang, Linlin; Cui, Shifang; Bi, Hongyan; Chen, Qiang; Kan, Mengfan; Wang, Cheng; Pu, Yu; Cheng, Hongxia; Huang, Bin (Frontiers in Neurology, 2024)
BackgroundEssential tremor (ET) is one of the most prevalent neurodegenerative disorders, with surgery serving as the principal treatment option. This paper presents a bibliometric analysis of research in the field of ET surgery from 2004 to 2024, aiming to identify current research hotspots and inform future research directions.MethodsThis study employs CiteSpace to analyze publication trends, countries/institutions, authors, keywords, and co-cited references in ET surgery, using the Web of Science core database from 2004 to 2024 to delineate the research pathways.ResultsA total of 1,362 publications were included in this study. The number of publications has shown steady growth over the analyzed period from 2004 to 2024. Research in this field was carried out in 58 countries and by 371 institutions. The United States had the highest volume of publications, with the University of California System identified as the most prolific institution. Dr. Michael S. Okun from the University of Florida was the most prolific author, also based in the United States. This study identified 879 keywords, with significant citation bursts noted in areas such as the caudal zona incerta, ventral intermediate nucleus, location, and MR-guided focused ultrasound. Among the top ten highly cited articles, five pertained to MR-guided focused ultrasound thalamotomy, two addressed localization techniques, and one focused on surgical targets.ConclusionThis study employs comprehensive bibliometric and visualization analyses to elucidate the evolution of research and identify emerging hotspots. The identified hotspots are as follows: First, deep brain stimulation (DBS), the most advanced technology in ET surgery, has room for improvement, especially in neuromodulation automation. Second, MR-guided focused ultrasound thalamotomy is a new surgical approach that requires further research on efficacy, safety, and side effect management. Third, novel surgical targets have demonstrated some efficacy, yet further research is essential to validate their effectiveness and safety. Lastly, localization techniques are fundamental to ET surgery, with ongoing efforts directed towards achieving more precise, individualized, and intelligent localization.